THE ROLE OF EMOTIONAL ATTACHMENT IN MEDIATING THE INFLUENCE OF PERCEIVED VALUE, PLAYER SATISFACTION, AESTHETIC QUALITY, AND FOMO ON THE INTENTION TO REPURCHASE MOBILE LEGENDS: BANG BANG SKINS - Muh.Fauzan Syarief; Michael Ricky Sondak (RADJA PUBLIKA, 2026)
The development of the digital gaming industry has driven increased consumption of virtual items, including skins in Mobile Legends: Bang Bang. Skins function not only as cosmetic elements but also as a means of self-expression, a status symbol, and a representation of a player's identity in the gaming community. This study aims to analyse the influence of perceived value, player satisfaction, aesthetic quality, and Fear of Missing Out (FOMO) on skin repurchase interest with emotional attachment as a mediating variable. The research used a quantitative approach through an online survey of 390 Mobile Legends: Bang Bang players who had purchased or used skins. Data were analysed using Structural Equation Modelling Partial Least Squares (SEM-PLS) with the help of SmartPLS 4. The results of the study show that perceived value, player satisfaction, aesthetic quality, and FOMO have a positive and significant effect on emotional attachment. In addition, emotional attachment has been shown to positively influence interest in repurchasing skins. The research findings also show that emotional attachment significantly mediates the influence of perceived value, player satisfaction, aesthetic quality, and FOMO on skin repurchase intention. These results indicate that emotional factors have an important role in explaining virtual item consumption behaviour in digital game players. Therefore, game developers need to develop strategies that strengthen players' emotional connections by increasing product value, the quality of the gaming experience, visual quality, and the exclusivity of virtual products.